Memory Strategies for Serial Recall in Adults with Intellectual Disabilities - Mitsuhashi, Shota; Hirata, Shogo; Okuzumi, Hideyuki (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
This study was conducted to investigate the memory strategy for serial recall in adults with general intellectual disability (ID) using the picture memory span task. Relations between memory strategies and two aspects of intellectual abilities, i.e., verbal and nonverbal abilities, were investigated. Study participants were 19 adults with general ID (i.e., ID of unknown etiologies). The picture memory span task, which can assess features of memory coding, was administered under four conditions: control, visually similar, phonologically similar, and long-name condition. The picture vocabulary test – revised (PVTR) and Raven color progressive matrices (RCPM) were conducted. Performance on the picture memory span task revealed that participants with ID used visual and verbal strategies for memory coding. Individual differences in verbal ability were interrelated with the degree of verbal strategy use. Results of this study suggest that features of memory coding of adults with ID do not contradict their level of intellectual development.